China's COVID-19 vaccine supplies to the Global South : between politics and business - Morgan, Pippa (Bristol shorts research., 2022)
This book unpacks the political economy of China's COVID-19 vaccine supplies to the Global South. Examining the political and economic forces at play, the book demonstrates how China's vaccine provisions have been determined by a complex set of commercial interests, domestic politics, and geopolitical relationships. The book sheds light on how domestic interests shape China's role in global governance and its international economic engagement. Its analysis contributes to broader academic debates on the politics and economics of crises, as well as offering new insights on how pre-existing political and market forces shape aid and trade in the context of crisis.